2017
DOI: 10.1016/j.apmr.2016.08.482
|View full text |Cite
|
Sign up to set email alerts
|

What Adherence Measures Should Be Used in Trials of Home-Based Rehabilitation Interventions? A Systematic Review of the Validity, Reliability, and Acceptability of Measures

Abstract: Current rehabilitation adherence measures are limited. Some possess promising validity and acceptability for certain parameters of adherence, situations, and populations and should be used in these situations. Rigorous evaluation of adherence measures in a broader range of populations is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 167 publications
2
68
1
2
Order By: Relevance
“…A recent literature review evaluated methods of measuring adherence in home‐based rehabilitation across a wide range of conditions . The review evaluated the quality of adherence measures in terms of validity, reliability, responsiveness to change and acceptability and concluded that self‐documented adherence diaries had moderate to high validity and acceptability rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent literature review evaluated methods of measuring adherence in home‐based rehabilitation across a wide range of conditions . The review evaluated the quality of adherence measures in terms of validity, reliability, responsiveness to change and acceptability and concluded that self‐documented adherence diaries had moderate to high validity and acceptability rates.…”
Section: Discussionmentioning
confidence: 99%
“…To assess acceptability of the home exercise diary, the rate of diary return and diary completion rates were recorded. Rates of 71% or higher represents high acceptability while rates of 70%‐50% were considered moderate . Consistent with the attendance criteria of PR, an acceptable completion rate was pre‐defined as reporting 70% of the exercise diary variables .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Desta forma, os resultados obtidos no estudo demonstram ser coincidentes com a generalidade da literatura, que revelam uma excelente adesão dos doentes aos programas domiciliários de RC. A alta adesão estará relacionada com maior probabilidade de manutenção de um estilo de vida ativo a longo prazo (Frost, Levati, McClurg, Brady, & Williams, 2016;Heron et al, 2016). Uma das primeiras motivações para a realização deste estudo foi a procura de uma resposta para a subutilização dos programas de RC.…”
Section: Discussionunclassified
“…Adherence to dose of exercise program should be measured in terms of duration, frequency, intensity, and correct performance of movement (Frost, Levati, Mcclurg, Brady, & Williams, 2018). A systematic review identified 61 measurement tools of adherence, out of which 29 were questionnaires, 29 were log diaries, 2 were visual analog scale, and one tally counter.…”
mentioning
confidence: 99%